2015 23rd Telecommunications Forum Telfor (TELFOR) 2015
DOI: 10.1109/telfor.2015.7377522
|View full text |Cite
|
Sign up to set email alerts
|

Low-cost planar MM-wave phased array antenna for use in mobile satellite (MSAT) platforms

Abstract: In this paper, a compact 8×8 phased array antenna for mobile satellite (MSAT) devices is designed and investigated. 64-elements of 22 GHz patch antennas with coaxial-probe feeds have been used for the proposed planar design. The antenna is designed on a low-cost FR4 substrate with thickness, dielectric constant, and loss tangent of 0.8 mm, 4.3, and 0.025, respectively. The antenna exhibits good performance in terms of impedancematching, gain and efficiency characteristics, even though it is designed using high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…Table 1 presents a comparison between the presented MRSA and the simulation only one reported in earlier work [17]. In addition, the table includes performance comparison with several conventional PAAs reported in literature [17], [45]- [51]. It is observed that presented MRSA is significantly improved in assembly size and experimentally verified as compared to [17].…”
Section: System Evaluationmentioning
confidence: 85%
“…Table 1 presents a comparison between the presented MRSA and the simulation only one reported in earlier work [17]. In addition, the table includes performance comparison with several conventional PAAs reported in literature [17], [45]- [51]. It is observed that presented MRSA is significantly improved in assembly size and experimentally verified as compared to [17].…”
Section: System Evaluationmentioning
confidence: 85%
“…Every element of the antenna are located sideways the two wide sides of a 130×75 mm 2 ground plane, which is almost the identical measurement of today's smart mobile phones. Eight antenna components are designed on two minor substrates which are placed perpendicular on the central system substrate [25][26][27][28].…”
Section: Design and Configurationmentioning
confidence: 99%
“…As shown, the design provides excellent radiation beams that could cover the half-space of the required radiation coverage for the smartphone. Another set of the compact linear array can be placed at the bottom side of PCB to achieve a full radiation coverage [31][32]. It is seen that the element provides 4~5 dBi maximum gains.…”
Section: The Performance Of the Presented Phased Array Mobile Antennamentioning
confidence: 99%